PENDIDIKAN ANAK PERSPEKTIF MUNIF CHATIB DAN RELEVANSINYA DENGAN PENDIDIKAN ANAK DALAM ISLAM - Sahwiyadi (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
This research head for knowing Munif Chatib’s child education perspective and it relevance with child education in Islam, which described into three focuses: (1) Munif Chatib’s child education cogitation background, (2) child education concept that Munif Chatib offered, (3) child education concept relevancy according Munif Chatib with Islamic child education. This research use Library Research with content analysis method. From this method, researcher analyzed former data in order to understand several Munif Chatib’s cogitation about child education and it relevancy with child education in Islam. The result showing that: (1) Munif Chatib education cogitation background is; first, lack of education distribution. Second, lack of parental attention to children. (2) Munif Chatib’s child education concept reveal that child education is a student development oriented effort not just their academic achievement, to develop ability and form nations’ prestige personality in order to educate nation’s life.